Aromaphytobalneotherapy in Treatment and Prophylaxis of Frequent Respiratory Infections in Children with Chronic and Disabling Diseases - O. M. Konova; E. G. Dmitrienko; T. G. Dmitrienko; E. V. Sakharova; A. M. Mamedyarov; N. I. Taybulatov (Union of pediatricians of Russia, 2016)
In children with chronic pathologies, co-occurring frequent respiratory infections of a prolonged course obstructs and reduce the effectiveness of rehabilitation measures, and adversely affect the adaptation reserves. Hydrotherapeutic factors are widely used for the prevention of colds in children from the first days of life. Addition to the water of medicinal and phytoaromatic preparations increases their efficiency. For patients with chronic pathology, when prescribing balneotherapeutic factors for treatment and prophylaxis of respiratory infections, it is important to take into account the potential risk of adverse effects on the symptoms of the underlying disease. Researches in patients with orthopedic, chronic gastroenterological diseases, spastic forms of cerebral palsy, with co-occurring frequent respiratory infections of a prolonged course in history revealed that addition of medicinal baths based on phytoaromatic preparation, containing eucalyptus oil, to the rehabilitation complex is an effective method of preventing and stopping initial symptoms of respiratory infections. It also contributes to the adaptation reserves of the organism, without adversely affecting the course of the underlying disease.